2019
DOI: 10.1101/514570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WNT/β-CATENIN modulates the axial identity of ES derived human neural crest

Abstract: 8The WNT/β-CATENIN pathway is critical for neural crest (NC) formation. However, the effects of the 1 9 magnitude of the signal remains poorly defined. Here we evaluate the consequences of WNT 2 0 magnitude variation in a robust model of human NC formation. This model is based on human 2 1 embryonic stem cells induced by WNT signaling through the small molecule CHIR9902. In addition 2 2 to its known effect on NC formation, we find that the WNT signal modulates the anterior-posterior 2 3 axial identity of NCCs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 127 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…Finally, because WNT signaling was found to modulate trunk versus cranial fate in Gomez et al. (2019b), we investigated the effect of different levels of WNT stimulation in the W2B3 system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because WNT signaling was found to modulate trunk versus cranial fate in Gomez et al. (2019b), we investigated the effect of different levels of WNT stimulation in the W2B3 system.…”
Section: Resultsmentioning
confidence: 99%
“…It is also in keeping with studies in amphibians that show Wnt signaling represses otx2 ( Otx-A ) expression and promotes expression of posterior neural genes (McGrew et al., 1995) as well as a recent study that describes how WNT directs cells toward a posterior identity in a manner that is time dependent and relies on CDX2 (Metzis et al., 2018). It also explains why titration of CHIR99021 results in a much-discussed “double peak” of neural crest induction efficiency (Gomez et al., 2019b).…”
Section: Discussionmentioning
confidence: 95%
“…In vivo , regional specification of developmental tissues into specific derivatives often occurs in response to different magnitudes of a particular signal, and this can be reflected in the differentiation of hPSC toward these lineages. WNT signaling has been implicated in the formation of axial progenitors and in the promotion of body axis elongation (Wilson, Olivera‐Martínez, & Storey, ), and recent publications have shown that the magnitude of WNT signaling is a key factor in the generation of hPSC‐derived neural crest corresponding to specific axial identities (Frith et al., ; Gomez et al., ; Hackland et al., ). Tightly controlled levels of WNT signal transduction using BLa could aid in these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Whether BSA has this effect by indirectly modulating the BMP pathway or by binding BMP ligands directly is unclear, but there is a good chance that this will be a problem encountered by others as the field continues to move toward highly defined, BSA‐free, conditions. Furthermore, this issue may not be restricted to protein agonists: in BSA‐free conditions, the concentration of CHIR99021 required to effectively induce cranial neural crest is approximately 25% of that required in the presence of BSA (Gomez et al., ; Hackland et al., , ; Leung et al., ; Mica et al., ; Tchieu et al., ). The capacity for BSA to confound attempts to understand hPSC differentiation is further enhanced by batch‐to‐batch variability which necessitates regular testing of BSA‐containing supplements (e.g., B27) if one is to attain optimal differentiation conditions.…”
Section: Role Of Bovine Serum Albumin (Bsa)mentioning
confidence: 99%
“…Under differentiation conditions, the hPSC-derived NMPs give rise to NC cells that express PG5-9 Hox genestypical of the thoracic neurectodermand can also give rise to sympathoadrenal cells (Frith et al, 2018). Other protocols for generating trunk NC cellsdefined by HoxC9 expression, limited mesenchymal potential, and the ability to produce sympathoadrenal cellsagain report the presence of an NMP-like intermediate state (Gomez et al, 2019b;Hackland et al, 2019). Notably, these trunk NC cell cultures exhibit a wider developmental potential than do avian trunk NC cells, as they are capable of forming smooth muscle and osteoblasts (Gomez et al, 2019b;Hackland et al, 2019).…”
Section: Lessons From Stem Cellsmentioning
confidence: 99%